ANALISIS MODEL MODEL KEBANGKRUTAN PADA PERUSAHAAN ASURANSI DI INDONESIA - Octaviani, Ermi; Situmeang, Chandra (Universitas Putera Batam, 2024)
Research on various models of financial distress analysis has been developed to predict the beginning of corporate bankruptcy, such as the Springate model, Altman Z-Score, Grover, and others. Each type of company provides varying accuracy in each analysis model based on variations in the findings of previous research investigations. This research aims to analyze whether the Springate, Altman Z